PROBLEMATIKA DEWAN PENGAWAS SYARIAH DAN SOLUSINYA - Isa Ansori (Nizham Jurnal Studi Keislaman, 2013)
Sharia Supervisory Board has an important role to ensure that the business has been runin accordance with Islamic Sharia principles. In fact, there are several issues that led tothe supervision mechanism will not deliver as expected, so it can make sharia businessdeviated from the provisions of Islamic law . There are four problems that need to beaddressed so that the oversight of Sharia Supervisory Board mechanisms run optimally,namely: legislation, organization and management, human resources and performance, aswell as facilities and infrastructure. Therefore, the state, the Sharia Supervisory Board,business managers, and academicians, needs to be involved to create a good oversightmechanism on Sharia Supervisory Board.